REPRESENTATION OF RELIGIOSITY IN THE FILM KOMANG BY NAYA ANINDITA: A ROLAND BARTHES SEMIOTIC ANALYSIS - Mhd. Arif Lubis; Fakhrur Rozi (Journal Analytica Islamica, 2026)
This study aims to analyze the representation of religiosity in Naya Anindita's film Komang through Roland Barthes's semiotic approach. This study departs from the importance of film as a popular media that not only provides entertainment, but also shapes social meanings regarding religion, culture, tolerance, and identity in a multicultural society. This study uses a qualitative descriptive method with data collection techniques through direct observation of film scenes, visual documentation, and relevant literature searches. Data are analyzed using three levels of meaning in Barthes's semiotics, namely denotation, connotation, and myth. The results show that religiosity in the film Komang is represented through worship practices, cultural symbols, traditional clothing, body gestures, prayers, and social interactions between characters from different religious and cultural backgrounds. At the denotative level, the film shows religious activities such as praying, prayer, group prayers, and traditional ceremonies. At the connotative level, these signs represent obedience, spirituality, respect for tradition, and tolerance. Meanwhile, at the mythical level, the film constructs the idea that religiosity is not merely ritualistic, but also serves as the foundation for morality, patience, acceptance, and social harmony. Thus, the film Komang represents religiosity as an inclusive human value and as a space for dialogue between love, faith, culture, and diversity.